The Disappearing Medium: Remarks on Language in Translation - Varsos, George (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2007)
This essay discusses problems pertaining to the disappearance of the language of the original text in the case of literary translation. After a reminder of recent criticism directed against ethnocentric translation strategies, the question is raised of the theoretical promises of alternative strategies. The text examines the different ways in which the relations between language and culture are theorized, taking two lines of inquiry that have strongly infl uenced contemporary translation theory: that of German Romanticism and that of Walter Benjamin.